The State and Directions of Development of e-Commerce in Ukraine - Kolupaieva Irina V.; Bezsonov Stanislav (Problemi Ekonomiki, 2023)
The rapid development of information technology changes the business environment around the world. Ukraine is no exception. The formation of the digital economy has become the basis of a new paradigm for the functioning of business entities. The availability of the Internet and the development of information technology, which are the main accelerators of the development of e-commerce, have contributed to a significant demand for online trade (e-commerce) in Ukraine. Nowadays, the number of companies that are switching to online platforms to sell their products is increasing. In Ukraine, online commerce covers a wide range of goods and services, ranging from food and household appliances to clothing, footwear and electronics. The aim of the study is to analyze e-commerce trends in Ukraine and ways of further development in the context of current challenges. The study defines that online commerce in Ukraine is a promising market with great potential for further growth and development. An analysis of the dynamics of the e-commerce market in Ukraine showed that by 2022 Ukraine demonstrated significant success in the e-commerce market. The largest increase of +48% compared to the previous period was observed in 2020 and was connected with the COVID-19 pandemic, which has become an accelerator of digitalization. In 2021, Ukrainian e-commerce market grew significantly – by 27%, compared to a global growth rate of 15%. Despite the fact that the number of purchased goods and services in Ukraine is gradually growing, these figures are still quite low compared to the average for EU countries. In order to determine the priorities of regulatory policy regarding the Ukrainian e-commerce market, based on the SWOT analysis, opportunities for further development and challenges that need to be addressed have been identified. Only with a balanced regulatory policy regarding the e-commerce market and the effective choice of appropriate regulatory levers can economic growth and the level of welfare of the population, the development of the country as a whole, be ensured.